IMPROVEMENT OF WORK QUALITY BY APPLYING ERGONOMIC APPROACH INCREASES PERFORMANCE OF TRADITIONAL PORTERS IN BADUNG MARKET DENPASAR - Hutagalung, Robert; Manuaba, A; Nala, I Gusti Ngurah; Sutjana, I Dewa Putu (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Female traditional porters work every evening at Badung market from 7 pm to3.30 am. Age interval of the porters is 18 – 40 years. The weight of goods carried by asingle porter is 60 – 100 kilograms plus 1-2 kilograms of the basket’s weight, carriedon the head. The distance of each porting activity is 100 meters. From ergonomicconcept, the burden is excessive and may cause injuries such as damage ofintervertebral discs, pain, excessive fatigue and head and neck muscles disorder. Thesymptoms are more obviously seen in those over 40 years old for most of them are notvery capable of working, even some of them need medical treatment. To overcome thisnon-ergonomic work condition, a work quality improvement was carried out to 11sampled porters, including work position, method, carrying weight and equipmentdesign in order to improve the unnatural work position and to give chance to them tohave an active rest as well as to alter the static work system to be more dynamic.Results of this study were: (1) average of pressure force on L5/S1 before improvementwas 7,967.65 ± 66.78 N and after improvement was 2,983.26 ± 16.63 N; (2) average ofmusculoskeletal complaints before improvement was 61.07 ± 0.72 and afterimprovement was 42.76 ± 1.21; (3) fatigue average before improvement was 77.44 ±3.93 and after improvement was 50.36 ± 2.21; (4) pulse rate average beforeimprovement was 150.61 ± 1.06 pulses/minute and after improvement was 119.51 ±1.39 pulses/minute; and (5) average productivity before improvement was 1.78 x 10-2 ±0.01 x 10-2 and after improvement was 2.24 x 10-2 ± 0.03 x 10-2. The results analysisshowed that improvement of work quality by applying ergonomic approach coulddecrease the pressure force on L5/S1 of 60.94 % (p<0.05), musculoskeletal complaintsof 29.99 % (p<0.05), level of fatigue by 34.97 % (p<0.05) and work load by 42.59 %(p<0.05), as well as could increase the work productivity to 26.04 % (p<0.05).Therefore, it is conclused that the improvement of work quality by applying ergonomicapproach increases performance of traditional porters.
Keywords: work quality, ergonomic approach, performance, traditional porters